2016
DOI: 10.1177/0960327116638725
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to triptolide affects follicle development in NIH mice

Abstract: Triptolide (TPL) is a main active compound isolated from Tripterygium wilfordii Hook f. Despite its positive therapeutic effect, the female reproductive toxicity of TPL is still the bottleneck of clinical application. The study was designed to investigate the adverse effects on mice ovary and underlying mechanism of TPL. Adult female NIH mice were treated with two therapeutic doses of TPL (25 and 50 μg/kg/d) for 50 days, respectively. Mice estrous cycle was detected by vaginal cytology method. Half mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 27 publications
(38 reference statements)
0
8
0
Order By: Relevance
“…TUNEL control tissue and vitrified sections were included in all evaluations, according to the manufacturer's recommendations. Only follicles with visible oocyte nuclei were analysed(Zeng et al, 2017).…”
mentioning
confidence: 99%
“…TUNEL control tissue and vitrified sections were included in all evaluations, according to the manufacturer's recommendations. Only follicles with visible oocyte nuclei were analysed(Zeng et al, 2017).…”
mentioning
confidence: 99%
“…that was reported to inhibit follicle growth and mutations, while promoting follicular atresia. The apoptotic index of GCs treated with triptolide at 50 μg/kg/day is reportedly 82.8‰ ± 7.1‰ (Zeng et al, 2017). In addition, treatment with plumbagin at 1, 5, and 100 μM for 24 h increased the proportion of apoptotic GCs and was associated with inhibition of the phosphoinositide 3‐kinase‐serine/threonine‐protein kinase/mechanistic target of rapamycin (PI3K/AKT/mTOR) signaling pathway (Cai et al, 2020).…”
Section: Natural Products and Bioactive Ingredients Of Tcm Induce Apo...mentioning
confidence: 99%
“…Earlier research found that GCs apoptosis was predominantly mediated by the celldeath ligand/receptor-dependent pathway [59]. Recent studies have paid more attention to ERS-mediated apoptotic pathways [60][61][62][63]. The ER is an important subcellular compartment involved in mitochondrion-dependent apoptosis [64,65], and ERS is a complicated adaptive reaction caused by certain stimulus [65].…”
Section: Sigma-1 Receptor Is Involved In Gcs Apoptosis and Ers-mediatmentioning
confidence: 99%